Interpretation of groundwater potential based on the Cooper Jacobs method combined with Schlumberger geoelectricity in Simpang Tiga Village, Pekanbaru City - Kurniawan, Joko; Muhammad, Juandi (Universitas Riau, 2025)
This study aims to analyze the aquifer parameter values including storativity, transmisivity, and hydraulic conductivity in Simpang Tiga Village, Pekanbaru City. This research is motivated by the community's increasing need for water due to higher population growth, and the Simpang Tiga Village which is close to the city center. Pumping test results using the Cooper Jacobs method showed an aquifer transmisivity value of 247.21 m2/day in the high category and a storativity value of 0.0845. The results of the geoelectrical test with the Schlumberger configuration obtained that the aquifer layer is in the fourth layer with a thickness of 11 m. The hydraulic conductivity obtained is 22.473 m/day and is included in the fast category.